Empagliflozin in acute myocardial infarction: the EMMY trial . (29th August 2022) - von Lewinski, Dirk; Kolesnik, Ewald; Tripolt, Norbert J; Pferschy, Peter N; Benedikt, Martin; Wallner, Markus; Alber, Hannes; Berger, Rudolf; Lichtenauer, Michael; Saely, Christoph H; Moertl, Deddo; Auersperg, Pia; et al.
Abstract: Aims: Sodium–glucose co-transporter 2 inhibition reduces the risk of hospitalization for heart failure and for death in patients with symptomatic heart failure. However, trials investigating the effects of this drug class in patients following acute myocardial infarction are lacking. Methods and results: In this academic, multicentre, double-blind trial, patients ( n = 476) with acute myocardial infarction accompanied by a large creatine kinase elevation (>800 IU/L) were randomly assigned to empagliflozin 10 mg or matching placebo once daily within 72 h of percutaneous coronary intervention. The primary outcome was the N -terminal pro-hormone of brain natriuretic peptide (NT-proBNP) change over 26 weeks. Secondary outcomes included changes in echocardiographic parameters. Baseline median (interquartile range) NT-proBNP was 1294 (757–2246) pg/mL. NT-proBNP reduction was significantly greater in the empagliflozin group, compared with placebo, being 15% lower [95% confidence interval (CI) −4.4% to −23.6%] after adjusting for baseline NT-proBNP, sex, and diabetes status ( P = 0.026). Absolute left-ventricular ejection fraction improvement was significantly greater (1.5%, 95% CI 0.2–2.9%, P = 0.029), mean E / e ′ reduction was 6.8% (95% CI 1.3–11.3%, P = 0.015) greater, and left-ventricular end-systolic and end-diastolic volumes were lower by 7.5 mL (95% CI 3.4–11.5 mL, P = 0.0003) and 9.7 mL (95% CI 3.7–15.7 mL, P = 0.0015), respectively, in the empagliflozin group, compared with placebo. Seven patients were hospitalized for heart failure (three in the empagliflozin group). Other predefined serious adverse events were rare and did not differ significantly between groups. Conclusion: In patients with a recent myocardial infarction, empagliflozin was associated with a significantly greater NT-proBNP reduction over 26 weeks, accompanied by a significant improvement in echocardiographic functional and structural parameters. ClinicalTrials.gov registration: NCT03087773. Structured Graphical Abstract: Structured graphical abstract A total of 476 people with acute myocardial infarction were randomized to either empagliflozin 10 mg or matching placebo once daily within 72 h of acute percutaneous coronary intervention. The change in NT-proBNP concentrations as well as echocardiographic functional and structural parameters over 26 weeks of treatment was evaluated. LVEF, left-ventricular ejection fraction; LVEDV, left-ventricular end-diastolic volume; LVESV, left-ventricular end-systolic volume; NT-proBNP, N -terminal pro-hormone of brain natriuretic peptide.